Cuff-Less Methods for Blood Pressure Telemonitoring - Bard, Dylan M.; Joseph, Jeffrey I.; van Helmond, Noud (Frontiers in Cardiovascular Medicine, 2019)
Ambulatory and home blood pressure monitoring is a mainstay in the diagnosis and treatment of hypertension. Traditionally, a cuff-based device is used in these settings; however, cuff-based devices have multiple limitations which have prevented their widespread use in ambulatory and home blood pressure monitoring. This has led to the development of new technologies which allow for blood pressure monitoring without the use of a cuff. These cuff-less devices allow for more frequent and simpler self-measurement of blood pressure, providing patients with autonomy and physicians with a more dynamic picture of their patients’ cardiovascular health. The two most common methods of cuff-less monitoring are arterial tonometry and pulse transit time. This review article aims to: (1) describe the fundamentals of cuff-less blood pressure monitoring; (2) present commercially available cuff-less devices which patients and physicians may encounter in practice; (3) outline challenges with current methodologies; and (4) describe potential future directions in research.